Peripheral Antinociception by Carbamazepine in an Inflammatory Mechanical Hyperalgesia Model in the Rat: a New Target for Carbamazepine? - Sonja Vučković; Maja Tomić; Radica Stepanović-Petrović; Nenad Ugrešić; Milica Prostran; Bogdan Bošković (Journal of Pharmacological Sciences, 2006)
Abstract.: This study investigated whether carbamazepine could produce local peripheral antinociception in a rat model of inflammatory mechanical hyperalgesia, and whether adenosine receptors are involved. Carbamazepine (100 – 1000 nmol/paw) coadministrated with a proinflammatory compound, concanavalin A, into the hind paw caused a significant dose- and time-dependent anti-hyperalgesia. Coadministration of caffeine (250 – 1000 nmol/paw), a non-selective adenosine-receptor antagonist, as well as DPCPX (10 – 30 nmol/paw), a selective adenosine A1-receptor antagonist, with carbamazepine, significantly depressed its antihyperalgesic effect. Drugs injected into the contralateral hind paw did not produce significant effects. These results suggest that carbamazepine produces local peripheral anti-hyperalgesia via peripheral adenosine A1 receptors. Keywords:: local carbamazepine, inflammatory mechanical hyperalgesia, adenosine A1 receptor